Medical students' experience of performing female pelvic examinations: Opportunities and barriers. (10th May 2017) - Bhoopatkar, Harsh; Wearn, Andy; Vnuk, Anna
Abstract : Background: Teaching and learning female pelvic examination within the undergraduate medical curriculum offers some potential challenges. One such is the extent to which students are provided practice opportunities with patients in the clinical setting. Aims: To quantify how many pelvic examinations, on real patients, have been performed by medical students at the point of graduation, and to explore opportunities and barriers to performing these examinations. Materials and methods: A retrospective study using a self‐completed, anonymous, electronic survey was developed as part of a multi‐centre study. Data were collected in the immediate period after graduation from the medical programs at the University of Auckland and Flinders University in 2013. An ordinal set of range categories was used for recording numbers of examinations. Results: The combined response rate for the survey was 42.9% (134/312). The median range category for the number of pelvic examinations performed in patients who were not in labour was 6–9 and in labour was 2–3. Thirty‐three percent of medical students had never performed a pelvic examination in labour. Male medical students performed significantly fewer pelvic examinations compared with female students. Self‐reported barriers to performing the pelvic exam include: gender of the student, 'gate‐keeping' by other health professionals, lack of confidence and patient factors. Conclusions: The majority of medical students have performed several pelvic examinations on real patients at graduation. Male gender and access being limited by midwives were the main barriers to performing female pelvic examinations. Medical curricula need to address these issues in the learning environment.